Revision of the subfamily Meyliinae De Coninck, 1965 (Nematoda: Desmoscolecidae) with a discussion of its systematic position - Decraemer, W.; Jensen, P. (Zoological Journal of the Linnean Society, 1982)
Locality: ; Cabinet:n1301
NeMys doc_id: 17023 NeMys doc_id: 6406